Method to quantify multi-dimensional benefits of social protection programs applied to school meals in Ghana - CGIAR Research Program on Policies, Institutions, and Markets (2021)
This methodology, which is relevant to a broad range of social protection programs that have multidimensional benefits spanning both human capital improvements and equity gains, was first described in a Discussion Paper published in 2021.